2012
DOI: 10.1136/bmjopen-2011-000671
|View full text |Cite
|
Sign up to set email alerts
|

NICE guidance: a comparative study of the introduction of the single technology appraisal process and comparison with guidance from Scottish Medicines Consortium

Abstract: ObjectivesTo compare the timelines and recommendations of the Scottish Medicines Consortium (SMC) and National Institute of Health and Clinical Excellence (NICE), in particular since the single technology assessment (STA) process was introduced in 2005.DesignComparative study of drug appraisals published by NICE and SMC.SettingNICE and SMC.ParticipantsAll drugs appraised by SMC and NICE, from establishment of each organisation until August 2010, were included. Data were gathered from published reports on the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Focusing on how they perform in practice and how much it costs for one additional quality adjusted life year. Similar organisations exist in both Scotland (Scottish Medicines Consortium, SMC) [76] and Wales (All Wales Medicines Strategy Group, AWMSG) [77].…”
Section: Box 2: United Kingdommentioning
confidence: 99%
“…Focusing on how they perform in practice and how much it costs for one additional quality adjusted life year. Similar organisations exist in both Scotland (Scottish Medicines Consortium, SMC) [76] and Wales (All Wales Medicines Strategy Group, AWMSG) [77].…”
Section: Box 2: United Kingdommentioning
confidence: 99%
“…However, an exception is the processing times for guidance on cancer drugs. Mason et al [20] and Ford et al [24] reported that for cancer drugs the STA process had not shortened the timelines. Casson et al [25] obtained similar findings; the group suggested that STAs of cancer-related technologies were slower to complete compared with non-cancer technologies, and that the difference was no longer significant when adjustments were made for other variables, including appeals.…”
Section: Discussionmentioning
confidence: 98%
“…Casson et al [25] obtained similar findings; the group suggested that STAs of cancer-related technologies were slower to complete compared with non-cancer technologies, and that the difference was no longer significant when adjustments were made for other variables, including appeals. Other possible explanations for the longer wait time for cancer drugs are that they are more expensive and that there is limited evidence at the time of their appraisal; Ford et al [24] considered that limited evidence at the time of appraisal generated delays when there were attempts to identify subgroups and stop/start rules for additional analysis. The use of independent evaluation groups was part of a broader strategy of encouraging independence and transparency in NICE's activities.…”
Section: Discussionmentioning
confidence: 98%
“…In their study comparing the NICE STA process with the Scottish Medicines Consortium process, Ford et al 3 found that, overall, the STA process reduced the average time to publication compared with NICE MTAs (median 16.1 months compared with 22.8 months). However, for cancer medications, the STA process took longer than the MTA process (25.2 months compared with 20.0 months).…”
Section: Historical Perspectivementioning
confidence: 99%